Mathematical modelling of water filtration - Chow, Ting Siong (2015)
The aim of this project is to develop a mathematical formulation called finite volume method which can provide stabilized numerical results for convection-diffusion problems. The finite volume method is studied and applied to investigate the problem of water filtration through a membrane. The values of concentration are obtained by using the explicit scheme method which is based on the finite volume method. To demonstrate the applicability of the method, an unsteady convection-diffusion problem is performed in the one-dimensional semi-infinite domain. The numerical results will then solve using MATLAB software program.